Bioremediation of environmental wastes: the role of microorganisms - Ayilara, Modupe S.; Babalola, Olubukola O. (Frontiers in Agronomy, 2023)
The growing rate of urbanization and industrialization has led to an increase in several types of pollution caused by the release of toxic chemicals to the environment. This is usually perpetuated by the manufacturing industry (e.g. detergent and dye), agricultural sectors (e.g. fertilizers and pesticides), mining industry (e.g. cyanide and sulphuric acid) and construction companies (e.g. cement and metals). These pollutants have adverse effects on the health of plants, animals, and humans. They also lead to the destruction of the microbial population in both aquatic and the terrestrial regions, and hence, have necessitated the need for remediation. Although different remediation methods, such as the physical and chemical methods, have been adopted for years, however, the drawbacks and challenges associated with them have promoted the use of an alternative which is bioremediation. Bioremediation involves using biological agents such as plants and microbes to remove or lessen the effects of environmental pollutants. Of the two, microbes are more utilized primarily because of their rapid growth and ability to be easily manipulated, thus enhancing their function as agents of bioremediation. Different groups of bacteria, fungi and algae have been employed to clean up various environmental pollutants. This review discusses the types, mechanisms, and factors affecting microbial bioremediation. It also recommends possible steps that could be taken to promote the use of microbes as bioremediation agents.